Spontaneous remission in adult acute myeloid leukemia in association with systemic bacterial infection: case report and review of the literature - Maywald, Ole; Buchheidt, Dieter; Bergmann, Jörg Stefan; Haferlach, Claudia; Ludwig, Wolf-Dieter; Reiter, Andreas; Hastka, Jan; Lengfelder, Eva; Hehlmann, Rüdiger (Annals of hematology, 2004)
Spontaneous remission of acute myeloid leukemia in the adult is a rare event. We report on a 31-year-old male patient suffering from acute myeloid leukemia (AML) M5a according to the French-American-British (FAB) classification with biphenotypic features in flow cytometric examination and severe bacterial infection with group G streptococci at the time of diagnosis. Because of sepsis and stable clinical conditions, chemotherapy was delayed and antibiotics were administered intravenously. Within 6 weeks a spontaneous remission of AML occurred. Remission lasted for about 2 months. At the time of relapse, a change in phenotype of the leukemic blasts with a loss of B-lymphoid markers could be demonstrated by flow cytometry. The patient was treated with an induction therapy according to the multicentric German AMLCG 2000 schedule. To our knowledge, this is the first report of a spontaneous remission in an AML FAB M5a associated with coexpression of myeloid- and lymphoid-associated antigens on the leukemic blasts. Possible mechanisms of this phenomenon are discussed with a review of the literature.